Creation of directed underwater explosion - Доля, Сергей Николаевич (Eastern-European Journal of Enterprise Technologies, 2015)
To create a shock wave with a flat or concave spherical front, the explosive is formed as a spiral with a constant or variable pitch and radius of the spiral winding. Then, the propagation velocity of the blast wave becomes smaller than the propagation velocity of the detonation wave, and the velocity of the blast wave can be varied by both a pitch, and radius of the spiral winding. Such spirals are evenly arranged over the lateral surface of the cone. With the spiral winding pitch hspiral = 40 cm, winding radius r0 = 25 cm, hexogen thread diameter of 1 cm, arrangement n = 36 of spirals over the lateral surface of the cone with an apex angle Θ = 450, a cone with a base diameter Dcone = 150 m, the mass of the explosive will be about 2 tons and, at a distance r = 20 kilometers from the cone, the pressure on the blast wave front will be P> 2 atm.